Effects of Leboyer childbirth on left- and right systolic time intervals in healthy term neonates - Nelle, Mathias; Kraus-Haas, Martina; Bastert, Gunther; Linderkamp, Otwin (Journal of perinatal medicine, 1996)
Der Artikel Effects of Leboyer childbirth on left- and right systolic time intervals in healthy term neonates wurde am 1. Januar 1996 in der Zeitschrift Journal of Perinatal Medicine (Band 24, Heft 5) veröffentlicht.